The Impact of Obesity on Mortality and Other Outcomes in Patients With Nonvariceal Upper Gastrointestinal Hemorrhage in the United States. Issue 2 (February 2019) - Abougergi, Marwan S.; Peluso, Heather; Mrad, Chebli; Saltzman, John R.
Abstract : Goals: To quantify in patients with nonvariceal upper gastrointestinal hemorrhage (NVUGIH) the relationship between obesity and mortality, disease severity, treatment modalities, and resource utilization. Background: NVUGIH is the most common gastrointestinal emergency. Study: Adults with a principal diagnosis of NVUGIH were selected from the 2014 National Inpatient Sample. The primary outcome was in-hospital mortality. Secondary outcomes were hemorrhagic shock, prolonged mechanical ventilation (PMV), upper endoscopy [esophagogastroduodenoscopy (EGD)], radiologic treatment, surgery, length of hospital stay (LOS), and total hospitalization costs and charges. Confounders were adjusted for using multivariable regression analyses. Results: In total, 227, 480 admissions with NVUGIH were included, 11.70% of whom were obese. Obese and nonobese patients had similar odds of mortality (aOR: 0.88; 95% confidence interval [CI]: 0.69-1.12; P =0.30), EGD within 24 hours of admission (aOR: 0.95; CI: 0.89-1.01; P =0.10), radiologic treatment (aOR: 1.06; CI: 0.82-1.35; P =0.66), and surgery (aOR: 1.27; CI: 0.94-1.70; P =0.11). However, obese patients had higher odds of shock (aOR: 1.30; CI: 1.14-1.49; P <0.01), PMV (aOR: 1.39; CI: 1.18-1.62; P <0.01), undergoing an EGD (aOR: 1.27; CI: 1.16-1.40; P <0.01), needing endoscopic therapy (aOR: 1.18; CI: 1.09-1.27; P <0.01), a longer LOS (0.31 d; CI: 0.16-0.46 d; P <0.01), higher costs ($1075; CI: $636-$1514; P <0.01), and higher charges ($4084; CI: $2060-$6110; P <0.01) compared with nonobese patients. Conclusions: Obesity is not an independent predictor of NVUGIH mortality. However, obesity is associated with a more severe disease course (shock and PMV), higher rates of EGD and endoscopic therapy use, and significant increases in resource utilization (hospital LOS, total hospitalization costs, and charges). Abstract : Supplemental Digital Content is available in the text.